The Analysis of the Physicochemical Properties of Benzocaine Polymorphs - Paczkowska, Magdalena (Molecules, 2018)
The study was a pioneering attempt to assess the influence of the structural polymorphism (forms I, II, III) of benzocaine on its solubility, apparent solubility, and chemical stability, which are vital parameters for preformulation and formulation work. The impact of differences in the solubility of selected polymorphs of benzocaine on their permeability through artificial biological membranes (PAMPA system) was evaluated. The polymorphs of benzocaine were obtained by means of techniques commonly used for the preparation of various pharmaceutical dosage forms: ball milling, micro milling, and cryogenic grinding, which allowed for the appearance or preservation of form III, the initial conformation of benzocaine. Ball milling resulted in the conversion of form III to I, whereas micro milling yielded form II. As a result of cryogenic grinding, form III of benzocaine was preserved. The identification of all polymorphic forms of benzocaine was confirmed via X-ray powder diffraction (PXRD) supported by FT-IR spectroscopy coupled with density functional theory (DFT) calculations. The differences in solubility, dissolution, and permeability through artificial biological membranes resulting from the polymorphic forms of benzocaine were established by using chromatographic determinations. Accelerated stability tests indicated that all polymorphic forms were chemically stable at a required level.